2007
DOI: 10.1002/jcp.21295
|View full text |Cite
|
Sign up to set email alerts
|

GHRH proliferative action on somatotrophs is cell‐type specific and dependent on Pit‐1/GHF‐1 expression

Abstract: To investigate the mechanisms by which the hypothalamic peptide GHRH influences cell division, we analyzed its effects on the proliferation of two different cell lines: CHO-4, an ovary-derived cell line, and GH3, a pituitary-derived cell line. We found that GHRH induces the proliferation of pituitary-derived cells but inhibits the proliferation of ovary-derived cells. We further characterized this dual effect of GHRH to find that the cytoplasmic signals induced by this hormone are similar in both cell lines. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 62 publications
1
14
0
1
Order By: Relevance
“…Indeed, we previously observed that the heterozygous invalidation of IGF-1R alters the development of the somatotropic axis, which is associated with a decrease of GHRH immune-reactivity in the median eminence at 10 days of age and a specific permanent pituitary hypoplasia of GH-producing somatotroph cells by 20 days of age. These findings are in agreement with previous studies that highlighted a strong implication of GHRH in the stimulation of proliferation and differentiation of somatotroph cells during the early postnatal period through an induction of Pit-1in developing pituitary [8]. Moreover, our previous report indicates that nutritional restriction during lactation in wild type pups, which decrease circulating levels of IGF-I, similarly induces a permanent pituitary hypoplasia in somatotroph cells by 20 days of age that is preceded by a transient decrease of GHRH expression level at 10 days of age.…”
Section: Introductionsupporting
confidence: 93%
“…Indeed, we previously observed that the heterozygous invalidation of IGF-1R alters the development of the somatotropic axis, which is associated with a decrease of GHRH immune-reactivity in the median eminence at 10 days of age and a specific permanent pituitary hypoplasia of GH-producing somatotroph cells by 20 days of age. These findings are in agreement with previous studies that highlighted a strong implication of GHRH in the stimulation of proliferation and differentiation of somatotroph cells during the early postnatal period through an induction of Pit-1in developing pituitary [8]. Moreover, our previous report indicates that nutritional restriction during lactation in wild type pups, which decrease circulating levels of IGF-I, similarly induces a permanent pituitary hypoplasia in somatotroph cells by 20 days of age that is preceded by a transient decrease of GHRH expression level at 10 days of age.…”
Section: Introductionsupporting
confidence: 93%
“…In general CDKN2A/p19Arf expression is regulated by two main pathways: oncogenes such as Ras and Myc in the so-called oncogene-induced senescence (OIS) or apoptosis (OIA), and DNA damage (Evan and d'Adda di Fagagna, 2009). We propose that the direct induction of p19Arf promoter by Pit-1 could be classified as OIA although Pit-1 is not an oncogene; but in a somatotroph Pit-1 is required to proliferate (Castrillo et al, 1991;Solloso et al, 2008). Thus, somatotrophs are protected against excessive proliferation through this RET/Pit-1/p19Arf pathway.…”
Section: Discussionmentioning
confidence: 99%
“…This induces the binding of cEBPa/CREB to an element of the Pit-1 promoter conserved in mouse, rat and humans with a huge induction of Pit-1 (Canibano et al, 2007;Garcia-Lavandeira et al, 2010). Pit-1 is an essential transcription factor for embryonic differentiation of pituitary precursors into somatotrophs and postnatal maintenance of the somatotroph phenotype (Castrillo et al, 1991;Pfaffle et al, 1992;Lin et al, 1993;Ward et al, 2006;Solloso et al, 2008). In a mature somatotroph, an over-the-level increase in the Pit-1 protein expression induces accumulation of p53 and apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…The major receptor that mediates the effects of GHRH in the extrapituitary tissues is SV1, a splice variant of the pituitary GHRH receptor that also has ligand-independent activity (Rekasi et al 2000, Kiaris et al 2002, Barabutis et al 2007. With regard to the effects of GHRH on proliferation, at the level of the signaling cascades activated upon binding of GHRH to its receptor(s), a role for mitogen-activated protein kinase (MAPK), and recently Pit-1 transcription factor has been recognized in pituitary cells (Pombo et al 2000, Solloso et al 2008. In breast cancer cells, Ras, Raf, and MAPK have been shown to play an essential role in the mediation of the proliferative effects of GHRH (Siriwardana et al 2006).…”
Section: Introductionmentioning
confidence: 99%